The Fourth Amendment in the Age of Persistent Aerial Surveillance - John Pavletic (2018)
If Big Brother made movies, persistent aerial surveillance would be its masterpiece. Small airplanes are rigged with high-tech cameras that can continuously transmit real-time images to the ground. The aircraft is able to monitor an area of thirty square miles for ten hours at a time. This technology allows video analysts to zoom in and track the location of vehicles, and even people. It was originally designed for military use during the Iraq War, but since then, it has been adapted for civilian applications. In 2016, the Baltimore Police Department contracted with Persistent Surveillance Systems to carry out a trial run of aerial surveillance over the city. The public was not informed that they were being watched every day. The Supreme Court has long held that aerial surveillance itself does not constitute a search for the purposes of the Fourth Amendment. The persistency of this new kind of reconnaissance changes the calculus. Specialized airplanes enable law enforcement agencies to survey sizable regions for hours on end. It is precisely this power that makes persistent aerial surveillance more like constant GPS monitoring, which the Court has already considered a search. These modes of long-term observation are intrusive and violate a reasonable expectation of privacy. Police action must be analyzed over time as a collective sequence of steps, not just an individual instance. The aggregate search can qualify under the Fourth Amendment, even if the individual steps did not. This is because prolonged surveillance reveals privacies and intimate details of life that short-term surveillance does not. Repetition, indeed habit, are cornerstones of personality and identity. People may reasonably expect some form of surveillance. People may also expect those observations to remain disconnected and nondescript. This technology presents intriguing opportunities for law enforcement departments, in the investigation of crime, the presentation of evidence at trial, deterrence and crime reduction, exonerating the wrongfully convicted, and even traffic management and highway control. These advantages are not enough—and will never be enough—to avoid the command of the Constitution. Over time, the public has become more accepting of the surveillance state. The Constitution remains a counter-majoritarian check on the government. Absent probable cause and a warrant, persistent aerial surveillance is an unreasonable search that violates the Fourth Amendment